Effect of Mass Addition on Physical Properties and Mechanical Properties of Agave Sisalana Fiber Composites - Epoxy - Antonius Sutanto Sinaga (Journal of Technomaterial Physics, 2022)
Research on the effect of the addition of Agave Sisalana fiber mass on physical properties and mechanical properties in sisal-epoxy fiber composites has been conducted as an alternative material for composite materials. Agave Sisalana fiber was taken from Sumber Agung Village of Rejo Stage District of Blitar Regency, East Java. Agave Sisalana fiber as a filler varies the composition of fiber mass 0 g, 2 g, 4 g, 6 g, and 8 g. The results of testing the physical and mechanical properties of Agave Sisalana fiber composites produce a density value of 1.064 g/cm3 - 1.335 g/cm3, water absorption 1.59% - 2.62%, porosity 1.7% - 3.5%, strong bending 54.542 MPa - 86.412 MPa, strong impact 29.92 kJ/m2 “ 98.32 kJ/m2, and strong tensile 1.983 MPa “ 12.368 MPa. The physical and mechanical properties testing results have met JIS A 5905:2003 Standards, namely strong bending >32 MPa, the density of 0.3-1.3 g/cm3, and water content < 25%. Agave Sisalana fiber composites with epoxy resin can be applied to car bumpers.